Development of the Understanding of Development: Critical Book Review of “Imagining the Post-Development Era” - Mehdi Hajamini; Mohammad Ali Aboutorabi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Although the birth of the first specialized development theories has so far lasted less than a century, the evolution of these theories has been controversial. While each theory attempts to explain the reasons behindthe  development and underdevelopment, it has been criticized by more recent theories, and hence the development economics is continuously developing. Meanwhile, perspectives of Dependency and Post-development regard other perspectives as a set of pessimistic, homological, and colonial theories, and called them “Theories of Western Development” and rejected them. The book of “Imagining the Post-Development Era” contains articles with different perspectives, but the book's theme and the ideas are based on Dependency and Post-development perspectives. The present paper seeks to develop the understanding of development. In addition, it offers suggestions for writing and editing similar books in the future.